# If x+ 3y = 3 and 2x-y = -2

### 1 Answer | Add Yours

x+ 3y = 3...............(1)

2x - y = -2..............(2)

We have a system with 2 equations and 2 variable, then we will use the substitution method to solve:

First let us rewrite equation no. (2).

2x - y = -2

==> y= 2x + 2 ...............(3)

Now we will susbitute y value from (3) into eq. (1):

==> x+ 3y = 3

==> x+ 3(2x+2) = 2

==> x+ 6x + 6 = 2

==> 7x + 6 = 2

==> 7x = -4

**==> x = -4/7**

Now subsittue x value in (3):

y= 2x + 2

y= 2(-4/7) + 2

= -8/7 + 2

= (-8+14)/7 = 6/7

**==> y= 6/7**